Inevitable Aging? - Baudisch, Annette (Springer, 2017)
The research presented in this monograph would not have been possible without the substantial support from many people. I am especially grateful to my advisors Linda Partridge at University College London and James W. Vaupel at the Max Planck Institute for Demographic Research. I was fortunate that they gave me the freedom to explore my intellectual interests while providing continuous support and advice. Linda and, even more, Jim often challenged me through detailed and intensive discussions.